SUBJECTIVE UNMET HEALTHCARE NEEDS AMONG VIETNAMESE OLDER PERSONS IN PRE AND POST COVID-19 - Tien Thuy Ngoc Doan; Long Thanh Giang; Tra Thu Doan (Indonesian Journal of Health Administration (Jurnal Administrasi Kesehatan Indonesia), 2026)
Background: The COVID-19 pandemic disrupted healthcare access, increasing unmet healthcare needs among older persons. Aims: This study examined changes in subjective unmet healthcare needs among Vietnamese older persons before and after the pandemic and identified contributing factors. Methods: Data from nationally representative surveys conducted in 2019 and 2022 were analyzed using Oaxaca–Blinder decomposition. Results: Subjective unmet healthcare needs declined between 2019 and 2022, with a significant reduction in unmet outpatient care. Education, social participation, and cognitive and memory impairments were key contributors. Conclusion: Policies should strengthen community outreach, caregiver support, age-friendly communication, and care navigation. Keywords: healthcare services, Oaxaca-Blinder decomposition, older persons, Viet Nam.